Implementation of the Merdeka Curriculum in Physical Education, Sports, and Health Subjects at Langsa City Public Elementary Schools - Puspita, Syaripah; Sinulingga, Albadi; Simatupang, Nurhayati (UNIB Press, 2024)
This study aims to evaluate the implementation of the Merdeka Curriculum in Physical Education, Sports, and Health (PJOK) subjects at Langsa City Public Elementary Schools. The focus of the research is on the learning process and the results achieved by students. This study uses observation and evaluation methods based on the standard learning process of PJOK. Data were collected through observation of learning activities that included introductory, core, and closing activities in classes VIII and IX. Data analysis in this study was carried out using the prerequisite test and t-test to test the research hypothesis. The results showed that the average value for preliminary activities was 45.5 (excellent category), core activities 50.09 (excellent category), and closing activities 15.13 (good category). Overall, the implementation of PJOK learning received a total score of 110 which is included in the excellent category. This study also found that the implementation of the Merdeka Curriculum at the school has been implemented optimally. The implementation of the Merdeka Curriculum in the PJOK subject at Langsa City Public Elementary Schools has been going well, having a positive impact on the learning process and student learning outcomes. Guidance from the driving school has assisted teachers in implementing meaningful learning by the new paradigm. The evaluation shows that the PJOK learning process not only improves students' physical fitness but also their social and individual development.